Creating a child feeding index using the demographic and health surveys: an example from Latin America - Ruel, Marie T.; Menon, Purnima (International Food Policy Research Institute, 2002)
Data from the Demographic and Health Surveys (DHS) for five Latin American countries (seven data sets) were used to explore the feasibility of creating a composite feeding index and to examine the association between feeding practices and child height-for-age (HAZ). Urban/rural differences were also examined...The data sets used were Bolivia, 1994 and 1998; Colombia, 1995; Guatemala, 1995 and 1999; Nicaragua, 1998; and Peru, 1996...This work shows that the data available in DHS data sets can be used for a variety of purposes, including to (1) describe and study the distribution of specific feeding practices by geographic area, or other characteristics of interest such as maternal schooling or household socioeconomic status; (2) create a child feeding index to quantify and illustrate associations between child feeding practices and child outcomes, thereby serving as an advocacy tool; and (3) identify practices and vulnerable groups that could be targeted by programs and policies to improve child feeding practices and overall child health and nutrition. In sum, greater use of the DHS data on child feeding practices should be promoted for research and analysis, as a source of guidance on program design and planning, and for advocacy.